Fellini and Popular Music - Masi, Leonardo (Załącznik Kulturoznawczy, 2022)
Through some examples taken from Nights of Cabiria, La Dolce Vita and The Voice of the Moon, the essay explores Federico Fellini’s attitude towards popular music, which plays a particularly relevant and original role in his films. Characters like Cabiria or Salvini identify themselves with popular music and are immersed in its particular taste, in contrast with other characters represented by classical music (Lazzari, Steiner, Gonnella). Popular music appears in some key moments of the three films and comes to unblock a stalemate on the level of the plot. Moreover it often creates “magical” moments in which the fourth wall is torn down and diegetic and extra-diegetic levels are messed up.